A Model to Assess the Economic Viability of Alfalfa Production Under Subsurface Drip Irrigation in California†. (16th December 2016) - Montazar, Aliasghar; Zaccaria, Daniele; Bali, Khaled; Putnam, Daniel
Abstract: This study was carried out to develop a model to explore the economic viability of subsurface drip irrigation (SDI) for alfalfa production in the major alfalfa production regions of California. Data from previously published studies on alfalfa under drip irrigation were applied to establish the relationship between hay yield and seasonal water use. A correction factor was defined to adjust the potential impacts of SDI due to regional differences in yield potential. A partial economic analysis was developed to assess economic benefits of SDI in alfalfa. The model predicted an additional 7.9 Mg ha −1 yield as a result of switching from surface flood irrigation to SDI, averaged across the principal alfalfa‐growing counties and regions in California. The hay yield improvements predicted by the model are in good agreement with the preliminary reports of improved hay yields from the 12 commercial farmers who have implemented SDI in Sacramento Valley, Low Desert, and Southern San Joaquin Valley regions. While the proposed model illustrated the potential profitability of SDI in alfalfa in several regions, further on‐farm experience and analysis would be required to confirm these results in practice. Copyright © 2016 John Wiley & Sons, Ltd.